1249 Operational delivery networks: opening the doors to shared learning. (17th August 2022) - Elson, Alexandra; Baird, Jim
Abstract : Aims: Children and young people (CYP) requiring Paediatric Critical Care (PCC) are cared for across 17 hospitals within the Thames Valley and Wessex (TV&W) Operational Delivery Network (ODN), with 2 hospitals delivering Level 3 Paediatric Intensive Care and a PCC transport service. Prior to the development of the ODN Morbidity and Mortality (MM) process, there was minimal opportunity for shared learning, monitoring of common themes and easily accessible external review panel members. A core element of improvement is the ability to learn, and as a network, we can ensure that learning can be amplified out of one Trust across the TVWPCCODN. To identify shared learning opportunities and common themes from incidents across the TVW PCC ODN, support local investigations ensuring consistency of approach and the furthest reach of learning points. The aim is to support local learning process with external members from ODN MM group Methods: MM process was developed collaboratively with TVW PCC ODN members, ODN clinical lead and manager, a MDT was formed known as the PCC TVW MM Group consisting of nurses, general paediatric consultants, ED consultants, PICU consultants, SORT consultants, Pharmacy, community. A defined inclusion/network definition was decided upon and cases are referred to the MM process by the local organisation or Retrieval Team. The M&M process provides external clinical experts to join the local learning panel consisting of as a minimum – general paediatrician/Paediatric ED consultant, PICU or Transport consultant, Nurse representative, plus any specialist members relevant to the case such as neurosurgical or cardiac teams. Following the learning panel, ODN MM panel will provide a summary and learning from the local teams' final report. This will be in the format Situation, Background, Assessment, Recommendations (SBAR). This is then discussed in the TV&W MM meeting and all comments feedback to the local team. Results: The TV&W MM process took time to embed, with initial large amounts of resistance to external members attending local investigations, although we have now support reviews of cases from 13/17 hospitals. Recurring themes from reviews include escalation delays with complex needs patients, medication errors due to variety of concentrations across the ODN, communication errors and delays due to specialist teams being first point of contact rather than transport team, raised lactate not triggering emergency procedures and red flags in critically ill children being missed by multiple healthcare providers. Cases are presented and learning shared at ODN education days and MM days with attendees from all local trusts. SBAR's and common themes are also disseminated across the ODN, common themes have been shared across the wider network including primary care, NHSE/I quality team and neighbouring ODN's. Conclusion: Despite early resistance to the M&M process, it has sparked culture change around shared learning across the region rather than individual trusts. The next steps include widening the group to include other regional ODNS, consideration of a governance lead within the TVW ODN and most importantly continuing to work with all providers to encourage the open learning culture and shared learning across the ODN.